Impact of eutrophication on the life cycle, population dynamics and production of Ampithoe valida (Amphipoda) along an estuarine spatial gradient (Mondego estuary, Portugal) - Pardal, M. A. (2000)
The life cycle, population dynamics and production of Ampithoe valida was studied from an intertidal mudflat in central Portugal, close to the northern limit of the species¹ distributional range in the eastern Atlantic Ocean. Sampling was carried out in eutrophicated areas, where macroalgae blooms of Enteromorpha spp. occur usually from January to early summer, and also in non-eutrophicated areas, with Zostera noltii meadows. A. valida showed a contagious distribution and the population density clearly changed during the study period along the eutrophication gradient. No migratory patterns were detected between the estuary and the sea, but migrations inside the estuary might have occurred. Females were morphologically recognisable at smaller sizes than males. Females reached sexual maturity before males, but males may live slightly longer than females. Females are iteroparous, producing 2, perhaps 3, broods. A 2-generation life cycle involving a short-lived (7 mo), fast-growing summer generation and a longer-lived (9 mo), slower-growing generation that overwinters is hypothesised. Ovigerous females were present year-round. Eggs, depending on the season, increase differently in volume during marsupial development. No correlations were found between fecundity (number of eggs) and the size of females. Along the eutrophication gradient no differences were found regarding the biology of the species. Besides these features, differences were observed between eutrophicated and non-eutrophicated areas with regard to productivity. Growth production (P) of A. valida in the most eutrophicated area was 0.098 g m-2 18 mo-1 and 0.64 g m-2 18 mo-1 in the Z. noltii meadows. P/B- and E/B- ratios (where E is the elimination production and B- is the average population biomass) ranged from 1.42 and 3.06 in the most eutrophicated area to 5.98 and 12.41 in the Z. noltii beds. To a certain extent, the increase of macroalgae biomass may favour A. valida populations, but extensive blooms affecting the whole area of distribution of this species will determine its disappearance